Long-term oncological outcome in patients with cervical cancer after 3 trimodality treatment (radiotherapy, platinum-based chemotherapy, and robotic surgery). Issue 13 (2nd April 2021) - Trifanescu, Oana Gabriela; Gales, Laurentia Nicoleta; Serbanescu, Georgia Luiza; Zgura, Anca Florina; Iliescu, Laura; Mehedintu, Claudia; Anghel, Rodica Maricela
Abstract : Abstract: Cervical cancer represents a general health issue spread all over the globe, which prompts the surge of scientific survey toward the rise of survival and condition of life of these patients. American and European guidelines suggest the open surgery, laparoscopic, and robotic surgery are the main therapeutic approaches for radical hysterectomy for patients with cervical cancer. This is the first survey to analyze the long-term oncological outcome of an extensive series of subjects cared for with multimodality treatment, here comprising robotic surgery. This study intents to evaluate the long-term oncological result in patients diagnosed with cervical cancer treated with radiotherapy (±chemotherapy) and robotic surgery compared with open surgery. Medical files of 56 patients diagnosed with cervical cancer who underwent a robotic hysterectomy and radiotherapy ± chemotherapy were retrospectively analyzed. The median age at diagnosis was 50.5 (range: 23–70). Eleven patients (19.6%) presented in an early stage (IB–IIA) and 80.4% advanced stage (IIB–IVA). Overall response rate after radiotherapy and chemoradiotherapy was 96.2%. Pathologic complete response was obtained in 64% of patients. After a median follow-up of 60 months (range: 6–105 months), 8 patients (14.2%) presented local recurrence or distant metastases. Disease-free survival (DFS) was 92% at 2 years and 84% at 3 and 5 years. Overall survival (OS) rates at 2, 3, and 5 years for patients with robotic surgery were 91%, 78%, and 73%, median OS not reached. OS was lower in the arm of open surgery (2, 3, and 5 years 87%, 71%, and 61%, respectively; median OS was 72 months P  = .054). The multivariate analysis regarding the outcome of patients revealed an advantage for complete versus partial response ( P  < .002), for early versus advanced stages ( P  = .014) and a 10% gained in DFS at 3 years for patients in whom chemoradiotherapy was administered (DFS at 3 years 75% vs 85%) in patients with advanced stages. Robotic surgery has a favorable oncological outcome when associated with multimodal therapy.